The Effect of Nepotism Perception on Career Anxiety: A Multiple Group Analysis - Sırkıntıoğlu Yıldırım, Şükran; Tohum, Enes Uğur; Esen, Ülkühan Bike (Turkish Academy of Sciences, 2024)
The study was conducted to investigate the effect of the nepotism perception of senior students and recent graduates on career anxiety and to measure how this effect differs according to demographic factors. Cross-sectional research methods and convenience sampling techniques were used among quantitative research methods. The research was conducted with 448 participants. According to the analysis results, there is a difference in the effect of nepotism perception on career anxiety according to gender. Considering the household's income level, the sub-dimension of family influence in the impact of nepotism perception on career anxiety differs in families with low-income groups. When parental attitude is considered, family influence differs in authoritarian families, while career choice differs in democratic families. The public sector differs in the sub-dimensions of career choice and family influence regarding the desired employment sector.
Keywords: Yükseköğretim Çalışmaları (Diğer); Higher Education Studies (Other); Career Anxiety; Nepotism; Demographic Attributes; University Students and Newly Graduates; Multiple Group Analysis; Kariyer Kaygısı; Nepotizm; Demografik Özellikler; Üniversite Öğrencileri ve Yeni Mezunlar; Çoklu Grup Analizi; 4. Education; 8. Economic growth; 1. No poverty; 10. No inequality; 16. Peace & justice